Faculty Development for E-Learning: A Multi-Campus Community of Practice (COP) Approach - Janet Reilly; Christine Vandenhouten; Susan Gallagher-Lepak; Penny Ralston-Berg (Online Learning, 2012)
Faculty development is a critical process, enabling instructors to remain abreast of new discipline specific content and innovations in the scholarship of teaching and learning. The explosion of online higher education and unbounded advances in technology provide examples and rationale for why faculty development for e-learning is needed. Literature on faculty development and e-learning is reviewed and a multi-campus faculty development program using distance technology and a community of practice model for nursing educators will be described. Successful strategies, barriers and an evaluation of the multi-campus faculty development model experience will be presented in a format that allows for replication across disciplines.